An economically viable hybrid additive manufacturing process for the fabrication of hierarchically controlled porous biodegradable Fe-Mn scaffolds - Sharma P.; Kumar A.; Kumar A. (My University, 2025)
The present work aims to develop a novel hybrid additive manufacturing (AM) route for fabricating biodegradable hierarchically controlled porous (HCP) Fe-Mn alloy-based scaffolds. Specifically, a systematic combination of polymer AM and loose powder sintering was used. The morphological, mechanical, magnetic and electrochemical properties of the Fe-30Mn scaffold were evaluated and compared with pure Fe. Proper bonding of particles with some random porosity was observed in the sample. XRD spectrum shows the presence of austenite (γ) and martensite (ε) phases in the sample. The prepared Fe-30Mn samples exhibited porosity = 23.08%, compressive yield stress = 127.28 MPa, modulus of elasticity = 25.9 GPa and corrosion rate = 0.75 mmpy. Moreover, the Fe30Mn sample showed weak magnetic properties, thereby making it MRI-friendly. Better properties of the prepared Fe30Mn sample as compared to pure Fe with close compatibility to the human bone were obtained. Additionally, complex structures of Fe30Mn using the developed methodology were fabricated to establish the efficacy of the process for biodegradable implant application. © 2024 Elsevier B.V.